Performance fitness level of football referees in Nigeria (2003)
A sample of 200 top male football referees participate in the study to determine the performance fitness level of football referees in Nigeria. The design for the study is ex-post facto research design. The participants are tested on speed, leg power and agility. The means, range, standard deviation, percentile rank of the scores of the tests are used to describe the data while the inferential statistics used is the students' t-test analysis to establish the significant differences between the subjects' determined values in the tested parameters and that of FIFA standards and Margaret, Safrit and Wood (1995) age and gender based average norm. The results show that the participants possess significantly superior speed, lower leg power and similar agility levels when compared with the stated norms. It is recommended that NFA/NRA should ensure that the referee's training include conditioning programmes that will develop their performance fitness levels.